Relationships between perceived motor competence and socioeconomic status of High School students (Research, Society and Development, 2020)
The research aimed to analyze the relationship between perceived motor competence and socioeconomic level of high school students of a State College of Maringá-PR. The sample consisted of 41 adolescents, 22 males and 19 females. The quantitative research, with descriptive character, had as instrument the Questionnaire for The Evaluation of Adolescent Motor Competence and the Protocol Criterion of Economic Classification Brazil (CCEB) of the Brazilian Association of Research Companies (ABEP). The data were analyzed by descriptive and inferential statistics with the aid of the SOFTWARE SPSS 22.0. The results indicated that 51.2% of the students fit into low perception levels of motor competence; there is no relationship between perceived level of motor competence and sex; there is a relationship between perceived motor competence and socioeconomic status, indicating that the higher the socio-economic level, the better the perceived motor competence. In light of the findings, it is concluded that, in this reality, there was a relationship between perceived motor competence and socioeconomic level in high school students.